Oxygenase Enzyme Activity and Compound Profile in Hydrocarbon Bioremediation by Pseudomonas aeruginosa and Rhodococcus erythropolis Consortium - Yanuar , Adi Tiya; Amin, Abd. Aziz; Salamah , Lutfi Ni'matus; Sujadi, Frentina Murty; Wiratno, Ekwan Nofa; Dewi, Citra Satrya Utama; Kurniawan, Andi (Jurnal Ilmiah Perikanan dan Kelautan, 2024)
Abstract Hydrocarbon contamination is one of the most significant environmental problems, including in the marine environment. Several methods, such as chemical and physical remediation, have been constructed to remediate pollutants but remain side effects and have a relatively high cost. Bioremediation is an alternative method for degrading contaminants due to its eco-friendliness and low cost. During bioremediation, the enzyme oxygenase is produced by bacteria to degrade pollutants. However, the oxygenation enzyme's activity and compound profile during this bioremediation process are still sparsely explored. This study aimed to analyze oxygenation enzyme activity and compound profiles during the hydrocarbon bioremediation process by bacterial consortia of Pseudomonas aeruginosa and Rhodococcus erythopolis. The materials of this research were the oxygenase enzyme activity, compound profile, and amount of BOD and COD during the bioremediation process. The results showed that the monooxygenase enzyme has activity between 0.257 and 3.859 U/mL. Meanwhile, the dioxygenase enzyme has activity between 0.579 and 5.402 U/mL. The final incubation compound profile found that Hexadecanoic acid methyl ester (C17H34O2) decreased by up to 47.66%. Moreover, BOD and COD reductions were 68.59% and 67.51%, respectively. This study concluded that oxygenation enzymes were produced to degrade pollutant compounds during the hydrocarbon bioremediation process. Further research is needed to improve the effectiveness of bioremediation by enhancing enzyme activity. Highlight Research The potential of hydrocarbon-degrading bacteria (Rhodococcus erythropolis and Pseudomonas aeruginosa) for pollutant degradation in the marine environment. Enzyme activity of hydrocarbon-degrading bacteria and degradation profile of pollutants. The dynamics of BOD and COD during the bioremediation process.